Bioinformatic Study of Transcriptome Changes in the Mice Lumbar Spinal Cord After the 30-Day Spaceflight and Subsequent 7-Day Readaptation on Earth: New Insights Into Molecular Mechanisms of the Hypogravity Motor Syndrome - Kuznetsov, Maksim Sergeevich; Lisukov, Artur Nicolaevich; Rizvanov, Albert Anatolevich; Tyapkina, Oksana Victorovna; Gusev, Oleg Aleksandrovich; Rezvyakov, Pavel Nicolaevich; Kozlovskaya, Inessa Benedictovna; Tomilovskaya, Elena Sergeevna; Nikolskiy, Evgeny Evgenievich; Islamov, Rustem Robertovich (Frontiers in Pharmacology, 2019)
The hypogravity motor syndrome (HMS) is one of the deleterious impacts of weightlessness on the human body in orbital space missions. There is a hypothesis that disorders of musculoskeletal system as part of HMS arise in consequence of changes in spinal motor neurons. The study was aimed at bioinformatic analysis of transcriptome changes in lumbar spinal cords of mice after the 30-day space flight aboard biosatellite Bion-M1 (space group, S) and subsequent 7-day re-adaptation to the Earth's gravity (recovery group, R) when compared with control mice (C group) housed in simulated biosatellite conditions on the Earth. Gene Ontology (GO) and Human Phenotype Ontology (HPO) databases were used to detect biological processes, molecular functions, cellular components and human phenotypes associated with HMS. Our results suggest resemblance of molecular changes developing in space orbit and during the post-flight recovery to terrestrial neuromuscular disorders. Remarkably, more prominent transcripome changes were revealed in R vs. S and R vs. C comparisons which are possibly related to 7-day recovery period in the Earth's gravity condition. These data may assist with establishment of HMS pathogenesis and proposing effective preventive and therapeutic options.